Metacognition and inner speech in individual with psychosis: a scoping review - Mohamad Danial Azizi Haji Mahadi; Gan Chun Hong (Penerbit Universiti Kebangsaan Malaysia, 2025)
Psychosis can be defined as individual’s experience of hallucination or delusions or both. It is regarded as one of the most challenging psychological illnesses to handle within the clinical walls. As of now, three main lines of treatment interventions (i.e. pharmacological treatment, cognitive behavioural therapy, and social cognitive Training) were deemed as having mixed findings or having questionable efficacy. This led to researchers in trying to find other means of psychological constructs to be incorporated into therapeutic interventions for people with Psychosis. Two of the proposed constructs were Metacognition (i.e. thinking about thinking) and Inner Speech (i.e. the internal experience of auditory language without the need to use covert language). This scoping review attempts to provide an overview on the extent of research that has been done relating to these three concepts (i.e. Metacognition, Inner Speech and Psychosis). Furthermore, this scoping review also attempts to identify any gaps in the literature that could aid and inform the direction of future research within this area of interest. The scoping review was done according to five-stage framework introduced by Arksey and O’Malley (2005). Results showed there seemed to be several theories being proposed from both field of Metacognition and Inner Speech in trying to explain Psychosis. However, these theories were not only contradictory to one another but also only rely on philosophical and psychological theories as there were no further scientific research done in trying to back up its claim. Further discussion and implication were presented in this article.